P1294AMBULATORY BLOOD PRESSURE PROFILE IN PERITONEAL DIALYSIS COMPARED TO HEMODIALYSIS AND CHRONIC KIDNEY DISEASE PATIENTS. (6th June 2020) - Alexandrou, Maria Eleni; Loutradis, Charalampos; Kouris, Nikolaos; Sarris, Dimitrios; Schoina, Maria; Tzanis, Georgios; Dimitriadis, Chrysostomos; Sachpekidis, Vasileios; Papadopoulou, Dorothea; Gkaliagkousi, Eugenia; Papagianni, Aikaterini; Parati, Gianfranco; et al.
Abstract: Background and Aims: Hypertension is highly prevalent in dialysis patients and is often poorly controlled. Data on the ambulatory blood pressure (BP) profile of patients undergoing peritoneal dialysis (PD) are scarce. The aim of this study is to compare the ambulatory BP profile of PD patients with that of hemodialysis (HD) and to pre-dialysis CKD patients. Method: 38 patients undergoing PD were matched in a 1:2 ratio for age, gender and dialysis vintage with 76 HD patients and in a 1:1 ratio for age and gender with 38 CKD stages 2-4 patients. Patients under PD and HD underwent 48-hour and CKD patients 24-hour ambulatory BP monitoring. BP levels were compared for the 48hour, 1st and 2nd 24hour, daytime and nighttime periods. Two-way mixed ANOVA analysis for repeated measurements was used to evaluate the effect of dialysis modality and time on ambulatory BP in PD and HD. Results: During all periods studied, SBP and DBP were numerically higher but not statistically different in PD than in HD patients. SBP was significantly higher in PD or HD compared with predialysis CKD (PD:138.38±20.97; HD:133.75±15.5; CKD:125.52±13.4 mmHg, p=0.003; PD vs CKD: p=0.003; HD vs CKD: p=0.041 accordingly); significant differences were also evident during the daytime and nighttime periods. DBP displayed a similar trend in the total period studied (PD:82.34±15.22; HD:80.47±11.13; CKD:76.81±7.82 mmHg, p=0.108), but the difference significant only during the second nighttime period. Repeated-measurements analysis showed no effect of dialysis modality and no interaction between modality and time on ambulatory BP during all periods studied. Conclusion: Average BP levels are similar between PD and HD patients, but higher for both groups compared to CKD counterparts. The dialysis modality had no significant effect on ambulatory BP profile.